Something to blog about - Norris, Shana (Amulet Books, 2008)
Boys, bullies, and blogs come together in a book that brings the popular online diary format to print. For fans of Lauren Myracle's ttyl, ttfn, and l8r, g8r, this fun, fast-paced book introduces an unforgettable and relatable heroine and features chapter openers designed to look like the pages of an online blog. An innovative debut, Something to Blog About is filled with the memorable missteps and heartfelt emotions of growing up